2010
DOI: 10.1159/000321801
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Resolution of a Radiation-Induced Cavernous Hemangioma of the Brain following the Use of Bevacizumab in a Child with Recurrent Medulloblastoma

Abstract: Radiation-induced cavernous hemangiomas (RICH) are a known complication of radiation exposure, especially in young children. The current treatment approaches to these lesions include observation and surgical resection. We report the case of a 4-year-old male with recurrent medulloblastoma who had resolution of an incidental RICH lesion while being treated with bevacizumab for his recurrent brain tumor. There was no evidence of worsening hemorrhage with this therapy and the RICH did not recur upon discontinuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…7,12 For numerous cases, use of bevacizumab to treat primary malignancies has reportedly produced incidental resolution of visceral hemangioma. 4,12 Common side effects of bevacizumab include hypertension, bleeding, and proteinuria. Temozolomide is an oral alkylating agent that acts by methylating DNA, leading to DNA breakage and apoptosis in actively dividing cells.…”
Section: Discussionmentioning
confidence: 99%
“…7,12 For numerous cases, use of bevacizumab to treat primary malignancies has reportedly produced incidental resolution of visceral hemangioma. 4,12 Common side effects of bevacizumab include hypertension, bleeding, and proteinuria. Temozolomide is an oral alkylating agent that acts by methylating DNA, leading to DNA breakage and apoptosis in actively dividing cells.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous Bevacizumab has been reported to be effective in the treatment of AVMs of patients with HHT, in radiation-induced cavernomas and in central nervous system hemangioblastomas [39][40][41][42]. Doses have ranged from 5 to 15 mg/kg IV every 2-3 weeks for 6-12 doses [37].…”
Section: Vegf Pathway Inhibitors (Ie Bevacizumab)mentioning
confidence: 99%
“…For instance, narrowing of vascular vessel lumen, ischemia and micro-infarction could cause microbleeds, while neoangiogenesis due to hipoxy-induciblefactor-1 release and vascular endothelial growth factor (VEGF) expression could originate cavernomas (22, 23). Aguilera et al reported an incidental remission of RT induced cavernoma during therapy with bevacizumab (a monoclonal antibody directed against VEGF), in a single patient with relapsed medulloblastoma(24). The authors hypothesized that resolution of the cavernoma was related to bevacizumab anti-VEGF activity.Three cases of superficial siderosis and two ischemic strokes also occurred.…”
mentioning
confidence: 99%